The software of automotive dictionary 2.0 - Đỗ Văn Dũng; Võ Xuân Thành (Journal of Technical Education Science, 2013)
This paper presented a high applicable dictionaries software. We has researched and designed an off-line dictionaries software named as “Automotive Dictionary, Version 2.0”. The dictionaries software integrates five types of dictionaries: English - Vietnamese, Vietnamese - English, abbreviations and acronyms, personal dictionary, favorite dictionary. Dictionaries software is programmed in C# programming language and the database management is based on Microsoft Access, which uses hyper text markup language (HTML) to format the database. Therefore, the interface was held and displayed in the way of science and spectacular, enabling users to use a very favorable way. The software has a very rich database, which is full of English, Vietnamese, abbreviations keys and videos, illustrations in automotive field. Apart from the words investigating function, the dictionaries software also has other useful features such as pronunciation, local data link to help users facilitate the investigation and learn how to pronounce the words correctly.